2016
DOI: 10.3109/13668250.2016.1223281
|View full text |Cite
|
Sign up to set email alerts
|

Factors predicting quality of life for people with intellectual disability: Results from the ANFFAS study in Italy

Abstract: Background: This study describes the socio-demographic, clinical and functional characteristics of a representative sample of services users in Italy. The supports provided by formal agencies, natural networks and actual levels of quality of life (QoL) were assessed. Methods: 1,285 individuals with intellectual and developmental disabilities (IDD) served by 23 different services participated to the study. The influence of availability of support strategies, environmental factors, client characteristics, person… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 35 publications
1
23
0
8
Order By: Relevance
“…Ésto enfatiza la importancia de tener en cuenta las opiniones de las PCDI acerca de su propia calidad de vida, puesto que no siempre coincidirá con las de sus familiares. Más aun, existe evidencia de que se obtienen mejores resultados cuando se consideran las opiniones de las PCDI al diseñar programas de intervención (Lombardi, Croce, Claes, Valdevelde & Schalock, 2016). Sin embargo, algunos estudios han encontrado asociaciones moderadas entre la percepción de las PCDI y la de los cuidadores, por lo que es importante continuar con estudios que permitan dilucidar dicha controversia (Córdoba-Andrade, Henao & Verdugo, 2016;Golubović & Škrbić, 2013).…”
Section: Discussionunclassified
“…Ésto enfatiza la importancia de tener en cuenta las opiniones de las PCDI acerca de su propia calidad de vida, puesto que no siempre coincidirá con las de sus familiares. Más aun, existe evidencia de que se obtienen mejores resultados cuando se consideran las opiniones de las PCDI al diseñar programas de intervención (Lombardi, Croce, Claes, Valdevelde & Schalock, 2016). Sin embargo, algunos estudios han encontrado asociaciones moderadas entre la percepción de las PCDI y la de los cuidadores, por lo que es importante continuar con estudios que permitan dilucidar dicha controversia (Córdoba-Andrade, Henao & Verdugo, 2016;Golubović & Škrbić, 2013).…”
Section: Discussionunclassified
“…A definição de DI não considera somente o QI, reforçando a funcionalidade da pessoa nos seus envolvimentos de vida (Morato & Santos, 2007). Os apoios são mediadores fundamentais entre o nível de funcionalidade atual (presente) e o nível de funcionalidade que cada indivíduo com DI pode vir a ter (desejado/optimal), sublinhando-se que são preditores da QV da população com DI (Lombardi, Croce, Claes, Vandevelde, & Schalock, 2016;. Por conseguinte, a definição de DI é mais abrangente do que uma condição biomédica ou um défice psicológico e educativo, abrangendo a interação entre o indivíduo e os seus contextos de vida, bem como os direitos e papéis exercidos nas suas comunidades (Schalock, Luckasson, Tassé, & Verdugo, 2018).…”
Section: Definição De Dificuldade Intelectualunclassified
“…Claes, Van Hove, Vandevelde, van Loon, & Schalock, ; Simões & Santos, ). Environmental variables, such as living independently, having a job and receiving needed support (Claes et al, ; Lombardi, Croce, Claes, Vandevelde, & Schalock, ; Memisevic, Hadzic, Zecic, & Mujkanovic, ; Simões & Santos, ), have been related to enhanced personal outcomes. Significant differences in QoL have also been described in relation to types of services received (Gómez, Peña, Arias, & Verdugo, ).…”
Section: Introductionmentioning
confidence: 99%
“…In terms of individual variables, QoL may also be influenced by a person's diagnostic and support needs (Arias et al, ; Claes et al, ; Gómez et al, ; Simões & Santos, ). Having mental health problems (Gómez et al, ), the level of IDD, and support needs are reported to negatively impact QoL (Arias et al, ; Claes et al, ; Lombardi et al, ; Memisevic et al, ; Simões & Santos, ). Another significant variable affecting the overall QoL scores is age, with older people reporting lower QoL scores (Gómez et al, ; Simões & Santos, ).…”
Section: Introductionmentioning
confidence: 99%